Evaluation and assessment of the wettabilty and water contact angle of modified poly methyl methacrylate denture base materials against PEEK in cast partial denture framework: an in vitro study - Joshua Narde; Nabeel Ahmed; Yuliia Siurkel; Maria Maddalena Marrapodi; Vincenzo Ronsivalle; Marco Cicciù; Giuseppe Minervini (BMC, 2024)
Abstract Introduction The prevalence of adults with partially dental arches is expected to be more than imagined and patients requiring replacement of missing teeth are slowly increasing in number too. Removable partial dentures are known to provide for substantial replacement for the missing teeth with also added advantages when compared to fixed or implant prosthesis, mainly in elderly patients. Denture base material performance and durability are greatly influenced by wettability and water contact angle. In the case of dentures; adequate moisture distribution is necessary to ensure excellent wettability which has an influence on comfort and oral health. The purpose of conducting this study was to find out whether the advancements made using PEEK (Polyether ether ketone) would prove to be more beneficial than the current upgrades in the current material spectrum. Materials and methods This study was performed under in vitro conditions. All the fabrication and processing was done only by one operator. The materials used were divided into three groups each comprising 20 samples. Group A was modified polymethylmethacrylate (Bredent Polyan), Group B was polyoxymethylene acetal resin (Biodentaplast) and Group C was PEEK. An Ossila Goniometer was used to measure the contact angle. The three types of liquids used for the testing included distilled water, natural saliva and mouth wetting solution (Wet Mouth Liquid, ICPA India). Human saliva was collected from an individual with no medical conditions and normal salivary secretion. Results The data was analyzed using One-way ANOVA test and a pairwise comparison using the Post Hoc Tukey's Honest Significant Difference. Table 1 consists of the mean water contact angles of the denture base materials and mean contact angles of various denture base materials. In saliva, mouth wetting solution and distilled water, the highest mean and least mean contact angle was seen in Polyan and Biodentaplast respectively. A signicant difference was seen between PEEK and Polyan and Biodentaplast and Polyan on further comparison. Conclusion From the resources and the materials at our disposal, it could be concluded that Polyan, Biodentaplast and PEEK and could be used as viable options in cast partial denture framework.